History of Transformation Processes in Trade Unions of Uzbekistan - Mamura Sharofidinovna Sirojiddinova; Muzaffar Ummatovich Kurbanov (Research Parks Publishing LLC, 2021)
Significant difficulties in the practical work of trade union organizations often occur due to the powerful influence of employers on them, betting on discrediting trade unions in the eyes of workers, on splitting the trade union organization. The deprivation of the rights of trade unions to manage social insurance, the weakening of their functions in the field of labor protection and supervision, the observance of labor legislation due to the removal of the state technical inspection from trade unions, the continuing trend of reducing the legal framework for the activities of trade unions, an anti-union campaign in the media and other actions, as well as the economic situation, it certainly weakens the trade unions and their authority. This article analyzes and covers the history of transformation processes in the activities of trade unions in Uzbekistan.